Exploring Research Directions on Waqf-Pesantren through Keyword Analysis: A Bibliometric Study - Purnama Putra; Mas Deden Tirtajaya (ARRUS Journal of Social Sciences and Humanities, 2026)
Waqf-based pesantren or waqf-pesantren is a type of property endowment owned by an individual for the benefit of the development and maintenance of an Islamic religious boarding school (pesantren). This study aims to analyze the development and research plans related to the topic of waqf pesantren based on research articles with the same topic. This study used a qualitative research design with a bibliometrics analysis approach. We used the Dimension database to search for research articles in this theme and obtained 191 research articles. Then, the data is processed and analyzed using the VosViewer application to find out the bibliometrics map of the development of research related to waqf-pesantren. The results of the study suggest that this topic has been researched extensively by same authors for the last couple of years. Furthermore, based on the bibliometrics keyword mapping, there are five clusters of the research paths related to waqf-pesantren. Those topics are productive waqf development in waqf-pesantren, the role of Islamic finance in waqf pesantren, micro waqf bank development in pesantren, the benefits of waqf fund in pesantren and pesantren endowment for education. Furthermore, the most widely used key words are waqf, pesantren, Islamic boarding school, development, and education.